Experimental investigation of the impact of geometrical surface modification on spray cooling heat transfer performance in the non-boiling regime. (April 2019) - Salman, Azzam S.; Abdulrazzaq, Nabeel M.; Oudah, Saad K.; Tikadar, Amitav; Anumbe, Noble; Paul, Titan C.; Khan, Jamil A.
Highlights: The impact of geometrical surface modifications on the thermal performance of the spray cooling system was studied. The maximum heat transfer enhancement was 80%, for surface modified with four circular and radial grooves. A significant effect of nozzle differential pressure has been found on spray cooling thermal performance. Abstract: An experimental investigation was conducted to study the impact of geometrical surface modification on the thermal performance of a spray cooling system. All experiments were performed using a closed loop spray cooling system. Deionized water was used as the working fluid. Three different modified surfaces were examined and compared with a plain copper surface under the same operating conditions. The first surface (M1) was modified with four circular grooves each having a width and depth of 0.5 mm and a pitch of 1.5 mm. The second and third surfaces (M2) and (M3) were modified with four circular grooves each overlaid with four and eight radial grooves, respectively. Each radial groove had width and depth of 0.5 mm. All surfaces were tested at three nozzle differential pressures: 80 kPa, 140 kPa, and 185 kPa. The nozzle-to-surface distance, coolant inlet temperature, surface temperature, and chamber pressure were maintained at 10 mm, ∼22 °C, <100 °C, and atmospheric pressure, respectively. The results indicated that the nozzle differential pressure had a significant effect on the spray cooling thermal performance of all surfaces. Furthermore, surface (M3) had the highest heat transfer enhancement ratio at all operating conditions, followed by surfaces (M2), and (M1), where the maximum heat transfer enhancements were 80%, 36.3%, and 28.7%, respectively. Thus, signifying that using surfaces modified with a combination of circular and radial grooves can enhance spray cooling heat transfer performance.